PENATAAN SERTIFIKASI KOMPETENSI AWAK KAPAL PENANGKAP IKAN DI INDONESIA - Muhammad Syarif Budiman; Budi Hascaryo Iskandar; Deni Achmad Soeboer (Jurnal Teknologi Perikanan dan Kelautan, 2016)
Competence crew of fishing vessels is one of the main factors supporting the success of fishing operations. Mastery of crew competence evidenced by a certificate of competence gained through education and training as well as certification testing crew of the fishing vessel by the competent authority. Crew competency standards fishing vessels must conform to the size of the vessel (ship’s length and gross tonnage) and area fishing operations. This study aims to assess the gap that occurs between the crew competency certificates fishing vessels with provisions of existing law in Indonesia as well as a contributing factor. Research has been done on the ship measuring more than 30 GT in Pelabuhanratu Nusantara Fishery Port and Fishing Port Ocean Nijam Zachman Muara Baru Jakarta. Primary data obtained from the evidence documents crew (BST, seaman books, Ankapin, Atkapin, SKK) who were on board. Secondary data were obtained from the Sijil Crew, SPB, vessel size (length and GT), the area of fishing operations as well as legislation on the manning of fishing vessels that apply in Indonesia. Data processing was performed using descriptive analysis with qualitative approach. The results showed the majority of the crew of the fishing vessel Indonesia does not have a certificate of competence in accordance with applicable regulations. This is caused by the publication dispensation SPB and certification test execution time constraints. The authorities should make clear deadline for publishing the dispensation of SPB and multiply the time and place of the certification test that is easily accessible by the crew.